Category Processing and the human likeness dimension of the Uncanny Valley Hypothesis: Eye-Tracking Data - Cheetham, Marcus; Pavlovic, Ivana; Jordan, Nicola; Suter, Pascal; Jancke, Lutz (Frontiers in Psychology, 2013)
The Uncanny Valley Hypothesis (Mori, 1970) predicts that perceptual difficulty distinguishing between a humanlike object (e.g., lifelike prosthetic hand, mannequin) and its human counterpart evokes negative affect. Research has focussed on affect, with inconsistent results, but little is known about how objects along the hypothesis’ dimension of human likeness (DHL) are actually perceived. This study used morph continua based on human and highly realistic computer-generated (avatar) faces to represent the DHL. Total number and dwell time of fixations to facial features were recorded while participants (N=60) judged avatar vs. human category membership of the faces in a forced choice categorisation task. Fixation and dwell data confirmed the face feature hierarchy (eyes, nose and mouth in this order of importance) across the DHL. There were no further findings for fixation. A change in the relative importance of these features was found for dwell time, with greater preferential processing of eyes and mouth of categorically ambiguous faces compared with unambiguous avatar faces. There were no significant differences between ambiguous and human faces. These findings applied for men and women, though women generally dwelled more on the eyes to the disadvantage of the nose. The mouth was unaffected by gender. In summary, the relative importance of facial features changed on the DHL’s nonhuman side as a function of categorisation ambiguity. This change was indicated by dwell time only, suggesting greater depth of perceptual processing of the eyes and mouth of ambiguous faces compared with these features in unambiguous avatar faces.